Asymmetric synthesis of alpha-mercapto-beta-amino acid derivatives: application to the synthesis of polysubstituted thiomorpholines - Candela-Lena, J; Davies, S; Roberts, P; Roux, B; Russell, A; Sanchez-Fernandez, E; Smith, A (2006)
Tandem conjugate addition of homochiral lithium N-benzyl-N-(α-methyl-p-methoxybenzyl)amide to tert-butyl cinnamate and enolate trapping with TsStBu proceeds with high diastereoselectivity to give a homochiral anti-α-tert-butylthio-β-amino ester. Stepwise deprotection gives the corresponding free α-tert-butylthio-β-amino acid without epimerisation. Tandem conjugate addition of homochiral lithium N-allyl-N-(α-methylbenzyl)amide to tert-butyl cinnamate and enolate trapping with TsStBu followed by conversion of the S-tert-butyl group to a disulphide, and reduction with Lalancette's reagent generates polysubstituted thiomorpholine derivatives. © 2006 Elsevier Ltd. All rights reserved.